Introduction to Qiyas and Maslahah Mursalah and Its Application In The Future - Remiswal Remiswal; Ayu Angraini; Asma Boti; Zerly Nazar (Program Studi Hukum Keluarga Islam, 2021)
This paper discusses qiyas and maslahah mursalah. The goal is to make it easier for us to establish a law. The data collection method that the writer uses is a literature study in the form of searching for books related to qiyas and maslahah mursalah. Qiyas In language (Arabic) means measuring, knowing the size of something, comparing, or equating something with another. For example قمت اللوب بالنراع which means